Research on the Social Service Competency Strategies for University Students in Yunnan Province - Jie, Chao; Yamgate, Kusuma; Areekul, Chananporn (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
As universities are increasingly expected to demonstrate tangible social impact, social practice has become a key pathway for cultivating students’ social service competency. However, many programs remain activity-driven rather than competency-driven, with fragmented frameworks and weak evaluation mechanisms. This study aims to (1) clarify the dimensional structure of university students’ social service competency, (2) construct a competency-based strategy system for students in Yunnan Province, and (3) evaluate its feasibility and perceived effectiveness. An explanatory sequential mixed-methods design was employed. A stratified survey of 382 undergraduates from four universities in Yunnan examined a proposed 10-dimension competency model. Reliability analysis and confirmatory factor analysis were conducted using SPSS and AMOS. Subsequently, a focus group (n = 7) and semi-structured interviews with students (n = 20) and service recipients (n = 10) were used to refine and validate the strategy system. Findings supported a stable 10-factor competency structure. Students demonstrated relatively stronger communication, teamwork, and social responsibility, but showed greater developmental gaps in innovation, leadership, cultural sensitivity, and practical execution. Based on these gaps, a three-level closed-loop strategy system (school–student–social ecosystem) was constructed and positively evaluated by stakeholders. The strategy system provides universities with an actionable framework linking competency diagnosis, targeted intervention, mentoring, and multi-source evaluation to improve both student development and service quality. Enhancing social service competency requires structured mentoring, role-based participation, and evidence-based assessment. A competency-oriented and ecosystem-supported model can strengthen the sustainability and effectiveness of social practice education in Yunnan universities.